Impact on the power mix and economy of Japan under a 2050 carbon-neutral scenario: Analysis using the E3ME macro-econometric model. (9th August 2022) - Lee, Soocheol; He, Yanmin; Suk, Sunhee; Morotomi, Toru; Chewpreecha, Unnada
ABSTRACT: This study uses the E3ME macro-econometric model to simulate what Japan's macroeconomy would look like and how Japan's energy composition would change if the country were to achieve carbon neutrality by 2050. The results indicate that renewable energy will account for about 90% of the power supply configuration in 2050, assuming nuclear power plants are phased out by 2040. It is also predicted that GDP will increase by 4.0%–4.5% compared with the baseline scenario and that employment will improve by 1.5%–2.0%, resulting in simultaneous achievement of carbon neutrality and economic growth. The main reasons for these projected outcomes are that increased investment in renewable generation capacity in the power sector would be accompanied by increased investment in decarbonization technologies across individual economic sectors, increased private consumption resulting from increased employment and energy efficiency savings, and an improvement in the trade balance due to a substantial reduction in fossil fuel imports. In addition, the costs of energy due to policies to reduce or eliminate carbon would rise by 45%–55% point at most above the baseline scenario even in 2050; however, this would be of little burden on the economy, considering the substantial reduction in fossil fuel energy demand. Overall, it is estimated that energy bills would be 45% lower for consumers and 11% lower for industry in 2050 compared with the baseline. Key policy insights The study shows that achieving climate neutrality does not require difficult trade-offs with economic growth. Instead, it can provide economic opportunities that arise from switching to renewables and decarbonization technologies. The rapid reduction in global renewable costs for wind and solar technologies means that the net zero transition does not have to rely on relatively more expensive nuclear power. The true costs of nuclear could be a lot higher when the costs of safety regulations are properly accounted for. Instead, investment in electricity storage should be prioritized. A well balanced decarbonization policy mix for each sector is required. Policy makers should not rely on carbon pricing instruments alone. Supporting policies such as R&D spending, renewable subsidies, regulations and energy demand reduction should also be considered.